PERANCANGAN APLIKASI MOBILE â€œMANDALUNGANâ€ SEBAGAI LAYANAN ONLINE POLRES KABUPATEN BREBES - Saputro, Godham Eko (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2020)
Brebes which is located on the north coast of Java has a large population and a wide area, must be conditioned safely and conducive by the local government. Although intense patrols are carried out by the Polres and Kodim, it is hoped that the pro-active and caring community will report the disorder of the Kamtibmas. The purpose of this study is to design a community service application to accelerate crime reporting and the Brebes citizen information center so that it is immediately handled by the District Police, 17 Sector Police and the Brebes Regional Government. This research method uses qualitative and the design of this application uses the MDLC method. The result of this study is an application called MANDALUNGAN which can be downloaded for free in the hope of reducing the disorder of the public order and becoming an ideal hope of the community towards the performance of the local government.